2015
DOI: 10.1103/physrevb.91.134423
|View full text |Cite
|
Sign up to set email alerts
|

Magnons and excitation continuum in XXZ triangular antiferromagnetic model: Application toBa3CoSb2O9

Abstract: We investigate the excitation spectrum of the triangular-lattice antiferromagnetic XXZ model using series expansion and mean field Schwinger boson approaches. The single-magnon spectrum computed with series expansion exhibits rotonic minima at the middle points of the edges of the Brillouin zone, for all values of the anisotropy parameter in the range 0 ≤ J z /J ≤ 1. Based on the good agreement with series expansion for the single-magnon spectrum, we compute the full dynamical magnetic structure factor within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 54 publications
11
51
0
Order By: Relevance
“…Meanwhile, we note that a Schwinger bosons mean field approach yields a spectrum with broadening due to deconfined spinons [14], bearing some resemblance to the observed results. After extending this approach to discuss spinon confinement as a more reliable description of a magnetically ordered state, it may offer a way of reconciling the discrepancy between theory and experiments.…”
Section: Nonlinear Spin-wave Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, we note that a Schwinger bosons mean field approach yields a spectrum with broadening due to deconfined spinons [14], bearing some resemblance to the observed results. After extending this approach to discuss spinon confinement as a more reliable description of a magnetically ordered state, it may offer a way of reconciling the discrepancy between theory and experiments.…”
Section: Nonlinear Spin-wave Analysismentioning
confidence: 92%
“…Introduction.-The S = 1/2 triangular-lattice Heisenberg antiferromagnet (TLHAF) is the paradigmatic example of a two-dimensional (2D) frustrated quantum magnet [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The combination of frustration, strong quantum fluctuations and low dimensionality is anticipated to produce strong deviations from semiclassical theories.…”
mentioning
confidence: 99%
“…Already the first theoretical studies of spin dynamics exposed salient deviations from non-interacting magnon scenario of linear spin-wave theory. Not only the spin waves are renormalized, sometimes changing their shape to produce roton minima around the M -points [84][85][86], but also the spectrum is washed out into a broad continuum at energies ω > J 1 [86][87][88][89]. These findings were initially interpreted as signatures of spinon excitationsan idea inspired by the work on square-lattice Heisenberg antiferromagnets.…”
Section: B Hexagonal Perovskites and Magnetic Excitationsmentioning
confidence: 99%
“…This fluctuating component can be represented by an RVB state and held responsible for various spectral features [90], including the broadening of spectral lines at high energies interpreted as a spinon continuum [91,92]. While a similar physics could be envisaged in the triangular case [85], and spinons may indeed account for a large part of the calculated spectral weight [88], non-linear spin-wave theory offered an alternative explanation in terms of interacting magnons. The roton minima can be reproduced by including the 1/S corrections [93,94] that are crucial in this case, given the nearly 60 % reduction of the ordered moment with respect to its classical value [95,96].…”
Section: B Hexagonal Perovskites and Magnetic Excitationsmentioning
confidence: 99%
“…A recent inelastic neutron scattering (NS) study of Ba 3 CoSb 2 O 9 [24] showed that even in presence of sizable perturbations [20,[25][26][27] relative to the pure QTLHAF, dynamical features are not captured by spin-wave theory (SWT). This observation suggests that alternative theoretical approaches are not only needed to describe spin-liquid states, but also to account for qualitative properties of the excitation spectrum of ordered magnets near their QMP [28,29].…”
mentioning
confidence: 99%